CD4+ T-cell transcription factors predict phenoconversion in idiopathic rapid eye movement sleep behavior disorder - Monica Pinoli; Michele Terzaghi; Franca Marino; Cristoforo Comi; Maurizio Versino; Marco Cosentino (Future Science OA)
Aim: Early biomarkers of phenoconversion to neurodegeneration are crucial to identify individuals at high risk. In patients with idiopathic REM sleep behavior disorder (iRBD), the strongest risk factor for neurodegeneration, CD4+ T cells exhibit a peculiar transcription factor pattern.Objective: To assess transcription factor mRNA levels in CD4+ T cells as predictive biomarkers of phenoconversion in iRBD patients.Methods: iRBD patients were followed prospectively. ROC curve analysis and Kaplan-Meier curves were used to assess the discrimination between converters and non-converters.Results: CD4+ T cells from converters had higher STAT1, and lower GATA3 and FOXP3 mRNA levels. Hazard ratio was 58.3 (95% CI: 6.2–547.1) for higher STAT1, 101.2 (95% CI: 16.8–609.4) for lower GATA3 and 15.7 (2.7–91.4) for lower FOXP3.Conclusion: STAT1, GATA3 and FOXP3 mRNA levels in CD4+ T cells are promising predictive biomarkers of phenoconversion in iRBD patients.